PSYCHOLOGISTS’ ROLE IN MENTAL HEALTH PROMOTION PROGRAM AT PUBLIC HEALTH CENTRE - Rina Tri Agustini; Diana Setiyawati; Anggun Wulandari; Dewayan Ekowanti; Retna Siwi Padmawati (The Indonesian Journal of Public Health, 2022)
Introduction: One of the initiations in Daerah Istimewa Yogyakarta is related to mental health workers who are expected to conduct mental health efforts, including optimal optimization promotive efforts through the placement of psychologists in Public Health Centre. Purpose of the study was to analyze psychologists' roles in mental health promotion programs at Public Health Centre in Sleman District. Methods: This was case study approach in qualitative study. Data collection through indepth interviews and focus group discussions were conducted with 32 informants selected by purposive sampling from two Public Health Centres in Sleman District based on extreme cases. Thematic analysis was performed considering four aspects of Normalization Process Theory. Result: Analysis results from psychologists' roles in mental health promotion program at Public Health Centre based on the Normalization Process Theory included, (1) coherence: a difference was observed with the presence of psychologists in the education system, community, and mental health services, (2) cognitive participation: participants were involved from inside and outside of Public Health Centre, (3) collective action: there was coordination between psychologists with cross-profession to promote mental health (4) reflexive monitoring: there were internal and external assessments of psychologists’ roles. Conclusion: The conclusion of this study is psychologists played their roles in mental health promotion programs such as communication, giving information, and education. Keywords: mental health promotion program, Normalization Process Theory, Public Health Centre, psychologists’ role